2018
DOI: 10.1002/jts.22268
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic Stress Disorder, Functional Impairment, and Subjective Distress in World Trade Center Disaster Workers

Abstract: Posttraumatic stress disorder (PTSD) is associated with functional deficits, poor physical health, and diminished quality of life. Limited research has examined PTSD symptom clusters and their associations with functioning and distress among disaster recovery workers, a population at high risk for PTSD due to potential for repeated trauma. The purpose of this study was to investigate associations between overall PTSD severity, as well as PTSD symptom clusters, and social and occupational functioning and subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Six studies have examined the association between functional impairment and PTSD symptom groups. The above-mentioned disaster worker study found that functional impairment was associated with groups B, C, and D (Hunnicutt-Ferguson et al ., 2018), but the above-mentioned combat veterans study found that functional impairment was associated only with groups C and D (Shea et al ., 2010). A study of tobacco-dependent veterans with chronic PTSD (Harder et al ., 2011) and a study of women with PTSD associated with childhood/adult physical/sexual assault (Shnaider et al ., 2014), both using the CAPS-IV, found functional impairment to be associated with both numbing and group D. A study of motor vehicle accident survivors using the CAPS-III-R found functional impairment to be associated with numbing, avoidance, and groups B and D, but the only consistent association was with the numbing subgroup (Kuhn et al ., 2003).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Six studies have examined the association between functional impairment and PTSD symptom groups. The above-mentioned disaster worker study found that functional impairment was associated with groups B, C, and D (Hunnicutt-Ferguson et al ., 2018), but the above-mentioned combat veterans study found that functional impairment was associated only with groups C and D (Shea et al ., 2010). A study of tobacco-dependent veterans with chronic PTSD (Harder et al ., 2011) and a study of women with PTSD associated with childhood/adult physical/sexual assault (Shnaider et al ., 2014), both using the CAPS-IV, found functional impairment to be associated with both numbing and group D. A study of motor vehicle accident survivors using the CAPS-III-R found functional impairment to be associated with numbing, avoidance, and groups B and D, but the only consistent association was with the numbing subgroup (Kuhn et al ., 2003).…”
Section: Discussionmentioning
confidence: 98%
“…Two studies examined the association of subjective distress and PTSD symptom groups. A study of disaster workers using the Clinician-Administered PTSD Scale (CAPS) for DSM-5 (CAPS-5) found that subjective distress was associated with PTSD groups B and C but not with group D (Hunnicutt-Ferguson et al ., 2018). A study of combat veterans using the CAPS for DSM-IV (CAPS-IV) found that subjective distress was associated with both groups C and D but not with group B (Shea et al ., 2010).…”
Section: Discussionmentioning
confidence: 99%
“…PTSD patients may use alcohol, drugs, caffeine, or nicotine or experience social withdrawal, depression, somatic distress, performance deterioration, interpersonal, and/or family conflict, etc. [1,7,28,30,31,34].…”
Section: Discussionmentioning
confidence: 99%
“…Among male utility workers on duty after the 9/11 attack, PTSD was significantly associated with sleep disturbance (β = 0.52, p-value < 0.01) [29]. Among rescue and recovery workers on duty after the 9/11 attack, workers with PTSD were more likely to experience early retirement and job loss [30] than those with no PTSD, and PTSD severity was positively associated with subjective distress and deficits in social and occupational functioning, over time [31]. Among policemen who responded to the 9/11 attacks and non-traditional responders, a significant relationship was observed between PTSD and lower respiratory symptoms [32,33].…”
Section: Effect Of Ptsd On the Health Of Workersmentioning
confidence: 98%
“…In this manner, the difference from a disaster is where it happens and the number of people affected or in other words, the availability of services (Khajehaminian et al, 2018;Tari-Verdi et al, 2018;Yafe et al, 2019). In this context, nurses and other first responders are responsible for caring for those suffering in times of crisis, pain and grief, both for victims and their families, and are therefore susceptible to emotional and psychological distress (Hunnicutt-Ferguson et al, 2018;Labrague et al, 2018;Morgan, 2016). Certainly, the impact of disasters on the general population and on the psychological problems of victims has received a lot of research attention (Kang, 2020;Resnick et al, 2020;Thoresen et al, 2019;Yoo et al, 2019).…”
Section: Introductionmentioning
confidence: 99%